2018
DOI: 10.3390/genes9090424
|View full text |Cite
|
Sign up to set email alerts
|

Human Age Prediction Based on DNA Methylation Using a Gradient Boosting Regressor

Abstract: All tissues of organisms will become old as time goes on. In recent years, epigenetic investigations have found that there is a close correlation between DNA methylation and aging. With the development of DNA methylation research, a quantitative statistical relationship between DNA methylation and different ages was established based on the change rule of methylation with age, it is then possible to predict the age of individuals. All the data in this work were retrieved from the Illumina HumanMethylation Bead… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
43
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 57 publications
(45 citation statements)
references
References 61 publications
(80 reference statements)
1
43
0
1
Order By: Relevance
“…The confusion matrix of Figure 3b shows the classification errors for the five-class label grouping. Finally, by examining the confusion matrix in the two previous cases, we re-labeled the data according to the three age classes obtained through the integration of classes (1, 2), (3,4,5), and (6,7,8,9,10). The accuracy of the model was 0.92 (+/− 0.12) using these three age groups.…”
Section: Classificationmentioning
confidence: 99%
See 4 more Smart Citations
“…The confusion matrix of Figure 3b shows the classification errors for the five-class label grouping. Finally, by examining the confusion matrix in the two previous cases, we re-labeled the data according to the three age classes obtained through the integration of classes (1, 2), (3,4,5), and (6,7,8,9,10). The accuracy of the model was 0.92 (+/− 0.12) using these three age groups.…”
Section: Classificationmentioning
confidence: 99%
“…DNAm, which often occurs in a CpG sequence, is an epigenetic sign and plays an important role in regulating cells to establish and maintain cellular identity. Various studies have shown that DNAm changes with age [4][5][6][7][8]. This change in DNAm can be disclosed at specific CpG-sites in all individuals, although individual differences may affect the "speed" of this change [6].…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations